An Analysis of the Financial Soundness of Polish Healthcare Organizations using the Altman Z-Score: A Closer Look at Regional Differences - Renata BURCHART; Małgorzata CYGAŃSKA; Apolonia JASKÓLSKA (Communications of International Proceedings, 2021)
The aim of this study was to examine regional differences in the financial soundness of Polish healthcare organizations using the Altman Zeta-score model. The Z-score model is widely used to examine the probability of bankruptcy in a company, and it is a reliable tool for measuring the financial soundness of a business. The study demonstrated that most Polish healthcare organizations are experiencing financial difficulties and that their financial soundness is compromised. The study also revealed significant direct relationships between the Z-score of healthcare organizations vs. the net monthly income per capita, employment-to-population ratio, and the youth dependency ratio in Polish counties.
Keywords: Healthcare organizations; Polish healthcare; Financial soundness; Altman Z.